ASPIRASI PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM PEMBERDAYAAN PEREMPUAN - Triana Dianita Handayani; Galang Geraldy; Launda Syandana; Enik Purwati; Moch. Ainul Yakin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The battle for political party legislative candidates ahead of the 2024 presidential and vice presidential general elections is increasingly heating up. Legislative candidates are diligently seeking the most votes in anticipation of the general election on February 14, 2024, targeting the involvement of women in the list of legislative candidates to remain at 37.7%. The general election ended with the women's quotas being fulfilled by various proposing parties. In Javanese philosophy, women are identified with 3M (Three M), namely Macak (adorned), Manak (giving birth), and Mapan (serving husband) or heaven and hell with the husband. A form of women's powerlessness in their nature which is always regulated in everyday life. How women can be empowered, they must have the skills to obtain the same/equal position and be respected. PDI-P's concern, seeing women in their electoral district experiencing failure in cultivating catfish in buckets (damber), encourage the initiative of PDI-P legislative candidate Indah Kurnia to assist in a form of her party's aspirations. The aim is for women to continue to be empowered so that they have income/capabilities/ insight by cultivating catfish in buckets using hydroponic technology. It is hoped that this aspiration will become an inspiration for powerless women to become empowered women.